Pengembangan Kompetensi Persiapan Pembelajaran Daring Di Era Pandemi Covid-19 - Yenni Djajalaksana; Teddy Marcus Zakaria; Doro Edi; Daniel Jahja Surjawan; Tiur Gantini; Djoni Setiawan Kartawihardja (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
The COVID-19 pandemic situation has forced many schools, universities, and many educational organizations in Indonesia into an unexpected situation. Given the lockdown, restrictions on social activities, and the implementation of social distancing by the Indonesian government, many educational institutions are struggling to adjust to the adaptation of new habits. As one of the educational institutions with qualified facilities, the Faculty of Information Technology (FTI) carried out community service programs by providing training for educators at the secondary and elementary school levels to be able to prepare interesting learning materials using elements of creativity in Slides, Videos, Blogs, and Vlogs and instill elements of Gamification for Learning in the learning materials. The implementation of community service is considered to have been able to enrich the knowledge of teachers and increase confidence in educating students in the era of adapting new habits that combine online and offline learning methods. The activities carried out for a private school in Bandung have been carried out well and received feedback from the participants of this community service program.